Compressibility behavior and lateral earth pressure of a marine soil mixed with tire crumbs. Issue 5 (4th May 2021) - Zokaei, Mahdiye; Karimpour-Fard, Mehran; Rezvani, Reza
Abstract: The reuse of scrap and by-product materials in civil engineering applications has increased in recent years due to environmental considerations. Soil-tire mixtures can be used in land reclamation in marine areas. The effects of tire crumbs on the compressibility behavior of a calcareous soil are evaluated in this study. Calcareous soils are generally located in tropical and semi-tropical areas near important strategic industries such as the Persian Gulf. In this study, the modification of effective stress theory for Qeshm calcareous soil-tire crumbs mixtures is investigated by using a tall oedometer apparatus. The effects of the compressible material on the lateral earth pressure coefficient of the mixtures are also studied. The results show that the tire crumbs have an influence on the overall compressibility of the mixtures. Increasing TC content results in decreasing the lateral earth pressure. In mixtures with 30% of tire crumbs K0 is reduced by approximately 110% and 66% in loose and dense samples, respectively. The increase in vertical stress reduces the effects of tire crumbs on soil-tire mixtures. The particle breakage of the mixtures is also decreased at a rate of about 0.06% per 10% of tire crumbs.